Job in the Light of Northwest Semitic. Volume I: Prologue and First Cycle of Speeches Job 1:1 - 14:22 - Michel, Walter L. (1987)
425-429: Index of Ugaritic Words; 430: Akkadian; 433-434: Eblaite; 435: Sumerian